Development of a mathematical model for microbial consumption of glucose and fructose during cocoa (Theobroma cacao L.) fermentation process - Daniel López-Puentes; Franyer López-Valiente; Daniel Rojas-Rodriguez; Diana Arias-Moreno (Microbiology Spectrum)
ABSTRACT A fundamental procedure for achieving the highest quality of cocoa is the fermentation of the bean carried out by microorganisms, a process in which the flavor and aroma of chocolate are developed. The objective of this research was to develop a mathematical model of microbial sugar consumption during the cocoa fermentation process. In this way, it is possible to obtain a mathematical tool that allows the representation of sugar consumption during the fermentation process. Initially, the need to construct a mathematical model was proposed due to its economic importance for small-scale producers in the national and international industries. In addition to the lack of control over the fermentation process, the complexity in terms of the microbial communities involved yeast (Y), lactic acid bacteria (LAB), and acetic acid bacteria (AAB). The methodological approach included (i) bibliographic review; (ii) specification of the parameters of the model, state, initial values, and equations; (iii) implementation of the mathematical model with the parameters, state, and initial values defined for each investigation; and (iv) validation of the model by comparing it with the experimental data from each publication. As a result, the model presented here for microbial sugar consumption during cocoa fermentation has the ability to represent each of the selected data points with significantly high precision. Furthermore, the proposed model aims to enhance the quality, efficiency, and sustainability of cocoa production, as well as contribute to scientific research related to this process. However, it is necessarily a simplification of the various biological processes that occur during cocoa bean fermentation.IMPORTANCECreating a mathematical model based on ordinary differential equations for glucose and fructose consumption by Y and LAB during cocoa fermentation is vital for advancing scientific and industrial practices. Cocoa fermentation is a complex, multi-step process involving microbial communities that play a key role in developing the flavor and aroma of chocolate. A robust mathematical model helps to understand the interactions between these microorganisms and sugar dynamics, providing a clearer understanding of the fermentation process.